Recurrent Feline Mammary Fibroadenomatous Hyperplasia in a Cat During Gestation - Nichanan Maneeganondh; Nitaya Boonbal; Panisara Kunkitti (Veterinary Medicine and Science)
ABSTRACT Feline mammary fibroadenomatous hyperplasia (FMFH) is an extensive proliferation of feline mammary tissues in response to endogenous or exogenous progestogens. The treatment of choice for FMFH is anti‐progestins or ovariohysterectomy (OVH). OVH if there is no intention of breeding the queen. This report describes a case of recurrent FMFH in an 11‐month‐old female Maine Coon cat. The condition was successfully treated with aglepristone during its first occurrence but recurred during the cat's subsequent gestation. OVH was performed along with aglepristone administration, resulting in complete regression of FMFH 21 days after aglepristone injection. The recurrence of FMFH successful treatment is well described; however, this case illustrates the necessity for further discussion regarding the utilisation of cats previously diagnosed with FMFH for breeding purposes.